Climate Risk Assessment and Infrastructure Resilience in India: An Integrated Econometric and Spatial Analysis Approach - Rami, Gaurang (JPAIR Multidisciplinary Research, 2026)
This study develops an integrated analytical framework combining climate risk assessment, econometric modelling, and spatial analysis to evaluate infrastructure resilience in India. Using district-level datasets aligned with IPCC projections, the analysis identifies pronounced regional disparities and a statistically significant upward trend in climate risk. The econometric results demonstrate that infrastructure systems designed using historical climate baselines are increasingly inadequate under future climate scenarios. The study addresses a critical gap by linking quantitative modelling with infrastructure planning and policy design. It proposes actionable strategies, including climate-informed design standards, district-level risk integration, and adaptive infrastructure investment frameworks, to strengthen resilience in high-risk regions.
Keywords: Climate Change Adaptation; Econometrics; Geographic Information Systems; infrastructure resilience; climate risk assessment; adaptive infrastructure planning; district-level analysis; Intergovernmental Panel on Climate Change projections; policy design; India